A Study of the Tennis Trust-Based System on the Psychology and Cognition of Amateur Tennis Enthusiasts - Fanghuan Yang; Yi-Sub Kwak (Behavioral Sciences)
Currently, amateur tennis events are developing rapidly, and the trust system has become a common rule, integrating considerations of entertainment, fitness, and cost control. However, human-centered trust system rules still face some controversy, and there is limited specialized research on the topic. This study explores amateur tennis players’ perceptions of the trust system rules. Using focus group discussions and interviews, we collected semi-structured interview data from 23 participants in tennis events. Based on grounded theory and the perceptual cycle model (PCM) framework, we developed a theoretical model of the tennis trust system and a model of the operational mechanism of the tennis trust system. Based on the grounded theory model results, four main factors influencing the tennis trust system were identified: interest orientation, information acquisition and judgment, communication and interaction, and development strategies. The operational mechanism model based on the PCM framework explains that the functioning of the tennis trust system includes five stages: foundation stage, trust-based emergence stage, monitor and detect stage, anticipate and respond stage, and development improvement stage. Among these stages, the anticipate and respond stage is crucial for the effectiveness of the trust system and is also the stage most prone to controversy. To address this, we propose targeted improvements to enhance the fairness of the tennis trust system and meet the needs of amateur tennis events.